The Effectiveness of Problem-Based Learning Model Assisted by Canva-Oriented Pancasila Student Profiles to Improve Scientific Literacy - Agus Wumu; Mursalin; Trisnawaty Junus Buhungo (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to describe the effectiveness of the Problem-Based Learning model assisted by Canva oriented to Pancasila Student Profiles and to analyze the effect of its implementation on scientific literacy skills in static electricity material. This research was conducted at SMP Negeri 1 Kwandang with 31 students in class IXA as subjects. This development research uses Research and Development (R & D) research with the ADDIE development model developed by Reiser and Mollenda, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The effectiveness test is carried out at the implementation stage. The results showed that the effectiveness of learning devices was seen through student activity data obtained by an average percentage of 93.27% obtained by very good criteria, and students' scientific literacy tests showed an increase in the N-gain score with an average N-gain score of 0.72 with high classification. This research concludes that physics learning tools that use the Problem-Based Learning model assisted by Canva-orientated Pancasila Student Profiles on static electricity effectively increase students' scientific literacy skills.